Vulnerable Funds? - Christoph Fricke; Daniel Fricke (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2017)
We develop a macro-prudential stress test for the fund sector by including the well-documented flow-performance relationship as an additional funding shock in the model of Greenwood et al. (2015). Here, systemic risks can arise due to funds' fire sales of commonly held assets. Using data on U.S. equity mutual funds, we explore the determinants of individual funds' vulnerability to systemic asset liquidations and highlight the importance of portfolio illiquidity.
Keywords: G10; G11; G23; 330